PENYULUHAN TENTANG BAHAYA KLORIN BAGI TUBUH MANUSIA DI DESA CANDIREJO - DIAN IKA PERBINA MELIALA; Rijayanti .; Feri Handika; Palas Tarigan (Jurnal Pengabdian Masyarakat Putri Hijau, 2020)
Background: Rice is a food that is a source of energy for mankind. At this time all kinds of food in Indonesia is not pure anymore and many contain harmful chemical substances. The use of chlorine in food is not unfamiliar. Therefore, chlorine is not recorded as Food Additives in bleach and flour clusters are allowed.Purpose: From this research is to know chlorine in branded and unbranded rice circulating in Medan city and to know the effect of Chlorine on branded rice and unbranded rice circulating in Medan city.Method: This research is descriptive. The object of the research is 5 (five) branded rice and 15 (fifteen) unbranded rice then examined in Laboratory of Qualitative Analytical Chemical Institute Deli Husada Deli Tua Health Institute by using color reaction method and settling reaction. Result: The results of the study did not contain chlorine content on branded and unbranded rice circulating in Medan.Conclusion: The content of chlorine in branded and unbranded rice circulating in Medan City is negative which means there is no chlorine content in branded and unbranded rice circulating in Medan City so it is safe for consumption, and the chlorine impact on the rice contained will resulting in the erosion of the intestinal mucosa in the stomach (corository), making it susceptible to ulcer disease. According to Permenkes RI No. 722 / Menkes / Per / XI / 12, stated that chlorine is prohibited to be used in rice. Advice from this research is Consumers should be more careful in choosing rice.